Penerapan Akuntansi Imbalan Kerja Jangka Pendek Pada PT Pendidikan Maritim Dan Logistik Indonesia - Agustiani, Santi; Rosita, Siti Ita; Suwarno, Suwarno (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Short-term employment remuneration is a work reward (other than a vacancy) that is expected to be completed entirely before 12 months after the end of the annual reporting period in which the employee provides the related services. The forms of remuneration for short-term work include salaries, benefits and bonuses.The purpose of preparation of this final task is to be able to know the recognition/measurement and presentation of short-term work remuneration as well as whether the application of the accounting of short term work compensation in PT PMLI has been in accordance with PSAK 24 on work reward. The results of the discussion showed that the measurement of short-term work remuneration (wages and benefits) for the staff member of PKWT (Specified-Time Work Agreement) is determined on the basis of contracts and employment regulations. Employment remuneration is recognised after the employee has completed the work and is recorded in the KSMU (Business Partnership) Labour and Labour account. Subsequently, the work remuneration will be presented on the operating burden on the loss profit report. It can be concluded that the application of short-term remuneration accounting to PT. PMLI has been in accordance with PSAK 24 on Employment Compensation.   Keywords: short-term remuneration accounting, PSAK 24